Effect of ginger in the treatment of nausea and vomiting compared with vitamin B6 and placebo during pregnancy: a meta-analysis. (2nd January 2022) - Hu, Youchun; Amoah, Adwoa N.; Zhang, Han; Fu, Rong; Qiu, Yanfang; Cao, Yuan; Sun, Yafei; Chen, Huanan; Liu, Yanhua; Lyu, Quanjun
Abstract: Introduction: Nausea and vomiting (NV) affect up to 85% of pregnant women, which has multiple effects on pregnancy outcome. The truth etiology of nausea and vomiting in pregnancy (NVP) is still unknown. Considering the potential teratogenic effect in fetus due to chemical drugs, ginger can be used to treat nausea and vomiting during pregnancy. Reports have shown that ginger can reduce the severity of NV, however, these results are controversial. Therefore, this meta-analysis aims to explore the effect of ginger in the treatment of nausea and vomiting during pregnancy compared with placebo and vitamin B6. Methods: The randomized control trials (RCTs) on the association with ginger and pregnancy-related nausea and vomiting were searched and identified in two databases Web of Science and PubMed (up to April 2019). Stata software was used to conduct meta-analysis. In addition, the source of heterogeneity explored by metaregression, sensitivity analysis, subgroup analyses, the publication bias were assessed by Egger's tests and Funnel plot, p  < .05 was considered to be significant. Results: Thirteen studies involving 1174 subjects were included in this meta-analysis. The result demonstrated that ginger intervention has significant effect in improving general symptom of NVP [OR = 7.475, 95% CI = (4.133, 13.520), I 2  = 30.1%], relieving severity of nausea [SMD = 0.821, 95% CI = (0.585, 1.056), I 2  = 38.9%], but not significant in reducing vomiting [SMD = 0.549, 95% CI = (−0.268, 1.365), I 2  = 91.4%], compared with placebo. Besides, ginger intervention has no significant effect on improving general symptom of NVP [OR = 1.239, 95% CI = (0.495, 3.102), I 2  = 57.3%], relieving severity of nausea [SMD = 0.199, 95% CI = (−0.102, 0.500), I 2  = 65.7%], reducing vomiting [SMD = 0.331, 95% CI = (−0.145, 0.808), I 2  = 85.9%], compared with vitamin B6. Conclusions: Ginger supplementation significantly relieve general NVP symptom and nausea compared with placebo, but no significant effect on vomiting. Moreover, ginger is more effective than vitamin B6 in treating NVP, although, there were no significant differences. Further, rigidly designed RCTs with larger sample sizes are needed to verify the effectiveness of ginger supplementation for treatment NVP compared with vitamin B6.